FLOWER CHARACTERISTICS OF LAMBS OBTAINED FROM MATING BUKHARA BROWN SHEEP ACCORDING TO COLOR EXPRESSION (Conferencea, 2023)
The purpose of this work is to present the results of the lambs flower characteristics obtained from the mating of the parents according to the expression of color.